2021
DOI: 10.1177/0049475520982770
|View full text |Cite
|
Sign up to set email alerts
|

Health research capacity in Nepal: Analysis of the trend and the role of local researchers

Abstract: Evidence-based decision-making is less common in low- and middle-income countries where the research capacity remains low. Nepal, a lower-middle-income country in Asia, is not an exception. We conducted a rapid review to identify the trend of health research in Nepal and found more than seven-fold increase in the number of published health-related articles between 2000 and 2018. The proportion of articles with Nepalese researchers as the first authors has also risen over the years, though they are still only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This may play a negative role to the submission from LMIC [ 24 , 37 , 38 ]. Active involvement of local researchers throughout the research process is essential as they often have a deeper understanding of the local context and needs [ 43 ]. Additionally, they are better positioned to advocate for implementing the research findings [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may play a negative role to the submission from LMIC [ 24 , 37 , 38 ]. Active involvement of local researchers throughout the research process is essential as they often have a deeper understanding of the local context and needs [ 43 ]. Additionally, they are better positioned to advocate for implementing the research findings [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the scarcity of publications from LMIC researchers can lead to reduced research activity focused on diseases predominantly affecting LMIC populations [ 14 , 23 , 24 , 37 , 38 , 40 ]. It is imperative to undertake efforts aimed at strengthening health research capacity in LMIC and addressing the inadequate representation of LMIC researchers in the editorial boards of hand journals [ 43 , 44 ]. The present study also revealed that when considering the membership of EBMs from LMIC standardized by their large populations, the relative percentage of LMIC representation appears significantly smaller [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%